The production and diffusion of policy knowledge: a bibliometric evaluation of the International Food Policy Research Institute - Pardey, Philip G.; Christian, Jason E. (International Food Policy Research Institute, 2002)
The published works of the International Food Policy Research Institute (IFPRI) represent the most immediate and tangible measure of the new policy-related knowledge attributable to the institute, its staff, and research partners. This study provides a quantitative assessment of the number, nature, form, and use of IFPRI's published products since 1979 and compares and contrasts that with the publication performance of several similar agencies, including the economics and social sciences programs of the Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT) and the International Rice Research Institute (IRRI) respectively, the Australian Bureau of Agricultural and Resource Economics (ABARE), the Bangladesh Institute for Development Studies (BIDS), and the now defunct Stanford University Food Research Institute (SFRI). Overall, IFPRI's circulated output is extensive, published not only in a broad portfolio of leading scholarly journals, but also in a wide range of books, technical reports, and extension documents. The amount of published output has tended to increase throughout IFPRI's history, and it continues to do so. Going beyond counting and classifying IFPRI's published record, we report the results of a bibliometric assessment of IFPRI and the comparison institutes for the period 1981–96 using the publication and citation performance details recorded in the Institute for Scientific Information's (ISI) Science Citation Index and Social Science Citation Index data bases. Citations to published literature are not indicative of an impact on policy or the economy generally but on further research and analysis. An analysis of coauthorship patterns provides an indication of impact too (more directly through the conduct of joint research), as well as indications of the way the research is carried out. Our analysis reveals the role IFPRI plays as a knowledge intermediary between the scholarly community and policy clienteles, but that a high proportion of its research collaborations leading to formal publications (and especially publications in the leading journals covered in ISI's data bases) involve researchers in advanced agencies. This partly reflects the limited capacity to perform food policy research in many developing countries — itself a reflection of local priorities for education and limited, long-term international support to increase scientific capacity in developing countries — and also underscores the role IFPRI could, and arguably should, play in redressing this state of affairs." -- Authors' Abstract.